Obstetric and Perinatal Outcomes in Women ≥40 Years of Age: A Retrospective Study About 421 Cases in Mahdia - Soumaya Kraiem; Leila Souilem; Dhekra Toumi; Haifa Bouchahda (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVES: All this study is aimed to evaluate obstetrical and neonatal outcomes among women age 40 years and older.